2019
DOI: 10.1021/acs.iecr.9b02656
|View full text |Cite
|
Sign up to set email alerts
|

POXINAR Membrane Family for Gas Separation

Abstract: Poly­(oxindolylidene arylene)­s (POXINARs), a family polymers with high performance in terms of thermal stability properties and with ether-bond-free aromatic backbones alternating with bulky, torsion resistant oxindolylidene fragments, have been synthesized by superacid catalyzed polyhydroxyalkylation, and their useful physical properties have been assessed to determine their performance as gas separation membranes. The room temperature synthesis allows a variety of fully soluble, high-molecular-weight polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 27 publications
0
17
0
2
Order By: Relevance
“…Common commercial nonfluorine-based backbones mainly include poly­(2,6-dimethyl-1,4-phenyleneoxide) (PPO), poly­(ether ether ketone) (PEEK), , and polysulfone (PSF). , However, when the main chain contains electron-withdrawing groups, it significantly reduces the alkali resistance of the membranes. Therefore, it is crucial to develop polymer backbones free of ether bonds for AEM materials. As displayed in Scheme a, among the possible designs for ether-bond-free backbones, superacid-catalyzed polymerization has been employed as an efficient method to fabricate poly­(arylene)-based AEMs. Yan et al developed a series of poly­(aryl piperidinium) membranes for AEMFCs; these rigid, high-molecular-weight backbones display good alkaline stability after 2000 h in 1 M KOH at 100 °C. Recently, Zhu et al reported novel poly­(isatin biphenyl) AEMs grafted with different side-chain cations.…”
Section: Introductionmentioning
confidence: 99%
“…Common commercial nonfluorine-based backbones mainly include poly­(2,6-dimethyl-1,4-phenyleneoxide) (PPO), poly­(ether ether ketone) (PEEK), , and polysulfone (PSF). , However, when the main chain contains electron-withdrawing groups, it significantly reduces the alkali resistance of the membranes. Therefore, it is crucial to develop polymer backbones free of ether bonds for AEM materials. As displayed in Scheme a, among the possible designs for ether-bond-free backbones, superacid-catalyzed polymerization has been employed as an efficient method to fabricate poly­(arylene)-based AEMs. Yan et al developed a series of poly­(aryl piperidinium) membranes for AEMFCs; these rigid, high-molecular-weight backbones display good alkaline stability after 2000 h in 1 M KOH at 100 °C. Recently, Zhu et al reported novel poly­(isatin biphenyl) AEMs grafted with different side-chain cations.…”
Section: Introductionmentioning
confidence: 99%
“…The superacid-catalyzed nonstoichiometric step polymerization of aromatic hydrocarbons with carbonyl compounds (polyhydroxyalkylation) is a relatively new and very efficient synthetic technique. , A remarkable feature of this method is the presence of the highly reactive intermediate carbinol formed after the first hydroxyalkylation step. Even more interesting is the fact that a 10–40% excess of the carbonyl compound significantly increases the polymer molecular weight and decreases the macrocycle fraction .…”
Section: Resultsmentioning
confidence: 99%
“…The methodology has been applied to synthesize polymers (e.g., poly­(aryl piperidinium, poly­(oxindolebiphenylylene), etc.) for the preparation of gas separation membranes, , fuel cells, and ultra- and nanofiltration. Inspired by these promising results we have extended the application of superacid-catalyzed polyhydroxyalkylation for the synthesis of wholly aromatic PIs.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the developed polymeric membranes and MMMs did not display a clear tendency to fracture; this is mainly due to its high thermostability with no significant weight loss below 500 °C (under air) as observed in thermogravimetric analysis (TGA) studies (Figure and Table S1), and glass-transition temperatures were not detected before its decomposition temperature. This behavior is analogous to that of similar polymers. , On the other hand, the obtained MMMs withstood harsh conditions during solvent evaporation (up to 200 °C, when NMP was used as a solvent) and gas transport measurements where pressures up to 2 bar were employed. This depicts the good thermal and mechanical stabilities, at least under the conditions studied, of the obtained MMMs.…”
Section: Resultsmentioning
confidence: 99%